Pedagogical Innovations for Enhancing ESP Students’ Speaking Competence in the Digital 21st Century: Challenges and Practical Implications - Anwar Taufiq; Yuriatson Jubhari; Nurul Amaliah (JURNAL PENDIDIKAN BAHASA DAN BUDAYA, 2025)
This study explores pedagogical innovations for enhancing English for Specific Purposes (ESP) students’ speaking competence in the digital 21st century. Employing a qualitative descriptive design, the research involved nine nursing students from IIK Pelamonia Kesdam XIV/Hasanuddin, Makassar. Data were collected through semi-structured interviews and classroom observations to examine how technology, contextual learning, and collaboration contribute to improving speaking performance. Thematic analysis revealed four major themes: (1) Technology-Enhanced Communicative Practice, highlighting the role of digital tools such as Zoom, Padlet, and YouGlish in promoting pronunciation accuracy, confidence, and learner autonomy; (2) Contextual Learning through Nursing-Based Scenarios, showing that authentic simulations and role plays improved students’ pragmatic competence and professional fluency; (3) Collaborative Digital Engagement, emphasizing peer learning, feedback exchange, and confidence-building in online group interactions; and (4) Challenges and Adaptation in the Digital Learning Environment, addressing students’ struggles with connectivity, anxiety, and digital literacy, yet underscoring their adaptability and resilience. The findings indicate that digital pedagogical innovation fosters communicative competence when technology is pedagogically integrated with contextual relevance and collaborative interaction. The study concludes that ESP teachers must act as facilitators who balance technological innovation with human-centered guidance to cultivate students’ confidence and professional communicative identity. These results provide practical insights for designing digitally enhanced ESP speaking curricula in higher education